MicroRNA-409-3p Targeting at ATXN3 Reduces the Apoptosis of Dopamine Neurons Based on the Profile of miRNAs in the Cerebrospinal Fluid of Early Parkinson’s Disease - Tan, Xuling; Hu, Junjian; Ming, Fengyu; Lv, Lingling; Yan, Weiqian; Peng, Xinke; Bai, Rongrong; Xiao, Qile; Zhang, Hainan; Tang, Beisha; Wang, Chunyu; Tan, Jieqiong (Frontiers in Cell and Developmental Biology, 2022)
Precise recognition of early Parkinson’s disease (PD) has always been a challenging task requiring more feasible biomarkers to be integrated to improve diagnostic accuracy. MicroRNAs (miRNAs) of cerebrospinal fluid (CSF) are believed to be potential and promising candidate biomarkers for PD. However, the role of altered miRNAs of CSF play in PD is unclear. Here, we recruited patients with early stages of PD and controls to analyze the expression of miRNA in CSF by the Next Generation Sequencing (NGS). Furthermore, we tested the levels of these miRNA in SH-SY5Y cells treated with MPP+ using real-time quantitative PCR. We found 21 miRNAs were upregulated in CSF of early PD patients and miR-409-3p, one of the identified 21 miRNAs, was further confirmed in SH-SY5Y cells treated with MPP+. Also, more cells survived in the overexpression of the miR-409-3p group when SH-SY5Y cells and mice were treated with MPP+ and MPTP, respectively. Mechanistically, we demonstrated the binding of miR-409-3p and 3’UTR of ATXN3 through a dual luciferase reporter gene assay. Moreover, miR-409-3p mimic reduced the aggregation of polyglutamine-expanded mutant of ATXN3 and apoptosis. Our results provide experimental evidence for miR-409-3p in CSF as a diagnostic marker of PD.